MULTI-CRITERIA DECISION ANALYSIS FOR CORROSION RISK ASSESSMENT OF BURIED WATER PIPELINES: AN ANALYTIC HIERARCHY PROCESS APPROACH - Omoruyi, Friday Osarenmwinda; Audu, Henry Agomemeh; Ilaboya, Idowu Rudolph (FUDMA JOURNAL OF SCIENCES, 2025)
The management of buried water pipeline systems requires reliable methods for assessing corrosion risk due to the complex interaction of pipeline characteristics and soil environmental conditions. This study develops a structured decision-support framework for pipeline corrosion risk assessment based on Multi-Criteria Decision Analysis (MCDA) using the Analytic Hierarchy Process (AHP). Pipeline attributes (length, thickness, burial depth, age, diameter, and internal pressure) and soil parameters (pH, electrical conductivity, salinity, and resistivity) were evaluated within the buried water distribution network of Edo State Polytechnic, Usen, Nigeria, which spans approximately 4,008.6 meters. Attribute weights derived from pairwise comparisons identified pipe age (0.22), soil resistivity (0.19), and burial depth (0.16) as the most influential factors. Lesser contributions were observed for pipe length (0.06) and diameter (0.08). The computed Pipe Condition Index (PCI) values ranged from 0.31 (high-risk) to 0.82 (low-risk) across pipeline segments. The AHP consistency ratio (CR) was 0.07, confirming the judgments reliability. These findings highlight the utility of MCDA for quantifying corrosion susceptibility in buried pipelines. The PCI framework provides a transparent and replicable tool for prioritizing pipeline maintenance and offers a foundation for future integration with artificial intelligence and GIS-based predictive systems.